The geometry and evolution of the deeply buried structural wedge in the kuqa fold-and-thrust belt: insights from numerical simulation - Chen, Weili; Wang, Wei; Zhao, Jiaqi; Yin, Hongwei; Hu, Fangjie; Zhang, Yong; Li, Zhihao; Jia, Dong; Zhang, Chunbo (Frontiers in Earth Science, 2024)
Numerical simulation is used to investigate the influence of thickness variation on the evolution of buried structural wedges, representing structures formed between two detachments. Simulations are based on the Kuqa fold-and-thrust belt, characterized by a tapered sedimentary sequence. Two sets of models were developed, one considering syn-tectonic sedimentation and the other without it. Model results indicate that an increase in thickness leads to larger intervals of thrusts, larger-scale thrust anticlines, and a reduced number of thrusts within the buried structural wedge, regardless of the presence of syn-tectonic sedimentation. The presence of syn-tectonic sedimentation is found to constrain the propagation of deformation within buried structural wedges, while increased thickness is observed to promote deformation propagation. Model results show that the deformation front expands toward the foreland from the thin model to the medium model and withdraws from the medium model to the thick model. This suggests that with the increase of wedge thickness, the restriction influence of syn-tectonic sedimentation on deformation propagation is more obvious than promotion. Model results show similarities in the structural features with the buried structural wedge in the Kuqa fold-and-thrust belt. With insights from numerical simulation, we suggest that the increased Mesozoic strata thickness from the west to east controls the structural variation along the strike. In the east, there are fewer thrust faults and larger fault intervals. Due to the restriction influence of the syn-tectonic sedimentation on the deformation propagation, the deformation front is an arc shape in the map view from west to east.